THE EFFECT OF GALLERY WALK STRATEGY ON THE STUDENTS’ ABILITY IN WRITING DESCRIPTIVE PARAGRAPH AT SMA NEGERI 2 BIREM BAYEUN ACEH TIMUR - NURHALIMAH, NURHALIMAH (BRIGHT VISION Journal of Language and Education, 2022)
This study was aimed to obtain empirical evidence about the effect of the gallery walk strategy on students’ ability in writing descriptive paragraphs in the tenth grade of SMA Birem Bayeun Aceh in 2020/2021 academic year. This research used quantitative method and the research design used is a quasi-experimental design. The population of this study were all tenth grade students of SMA Negeri 2 Birem Bayeun Aceh Timur. The sample technique used total sampling that consist of 47 students. The sample are divided into two groups: class X MIA1 as an experimental class consist of 24 students and X MIA2 as a control class consist of 23 students. The instrument of this research was written test. The results and the effect size of this study were obtained from data calculations using t-test with a significance level of (α) =0,05. The results showed that the post-tests’ mean score in the experimental class was 78,45 while in the control class it was 60,26. thus means the post-tests’ mean score in the experimental class is higher than the control class (78,45 > 60,26). Therefore, the statistical hypothesis test showed that the ρ-value of the post-test and the gained score is 0.000 < sig α 0,05. The effect size of this result is 1,53. It can be conclude that the alternatives hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. It means that the gallery walk strategy was significant effect on the students’ ability in writing descriptive paragraph at SMA Negeri 2 Birem Bayeun Aceh Timur in academic year.